2004
DOI: 10.1002/pd.945
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic biometrical range of external genitalia differentiation in the first trimester of pregnancy: analysis of 2593 cases

Abstract: Sonography is a reliable method for the study of the morphological development of the external genitalia in fetuses 'in vivo'; it is possible to assign fetal gender in 95 to 99% starting at a BPD of 20 mm and to achieve an accuracy rate of 99 to 100% from a BPD of 22 mm, but fetal sex assignment should not be undertaken below a BPD of 22 mm, and especially not in cases where fetal sexing affects pregnancy management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 24 publications
0
21
0
4
Order By: Relevance
“…With a cut-off of 4.8 mm a sample of 300 women (mean gestational age 12 WG + 3 days), the sex was correctly determined by ultrasound in 87 % of the males and 89 % of the females. [14,3,5,[15][16][17][18][19]8,20,7,6,21] They found that ultrasound fetal sex determination gave a sensitivity and specificity of 100% from 13 WG but that sex determination was difficult between 11 and 12 WG. However, in this review sex was not evaluable in 7.5 to 40.6 % of cases depending on the series.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With a cut-off of 4.8 mm a sample of 300 women (mean gestational age 12 WG + 3 days), the sex was correctly determined by ultrasound in 87 % of the males and 89 % of the females. [14,3,5,[15][16][17][18][19]8,20,7,6,21] They found that ultrasound fetal sex determination gave a sensitivity and specificity of 100% from 13 WG but that sex determination was difficult between 11 and 12 WG. However, in this review sex was not evaluable in 7.5 to 40.6 % of cases depending on the series.…”
Section: Discussionmentioning
confidence: 99%
“…This involved measuring the angle of the genital tubercle to a horizontal line through the lumbosacral skin surface in a mid-sagittal plane with the fetus in a natural position [3,4]. This method gave a 100% sensitivity in fetal sex determination after 13 WG but a lower sensitivity between 11 and 12 WG [3,[5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Hasta la fecha existen escasos trabajos publicados que valoren la precisión de la determinación ecográfica del sexo fetal durante el primer trimestre (3)(4)(5)(6)(7)(8)(9)(10)(11). El propósito de este trabajo es valorar la precisión de la determinación ecográfica del sexo fetal entre las 11-13+6 semanas de gestación en una serie prospectiva y grande de pacientes, así como determinar las variables ecográficas relacionadas con esta precisión.…”
Section: Introductionunclassified
“…É consenso que a ultra-sonografia tem acurácia muito baixa (cerca de 60%) no diagnóstico do sexo fetal antes da 12 a semana de gestação [2][3][4][5][6][7][8] . Entre a 12ª e a 13ª semana, a literatura apresenta resultados variados (75 a 99%), com boa acurácia (cerca de 100%) apenas a partir da 14 a semana de gestação [2][3][4][5][6][7][8] . Sob a ótica da embriologia, esse período pode ser considerado tardio, já que a diferenciação da genitália fetal se inicia pelo menos duas semanas antes 9 .…”
Section: Introductionunclassified